A heat pipe internally-cooled membrane-based liquid desiccant dehumidification system - Wang, Yuhao (2023)
In recent years, membrane-based liquid desiccant dehumidification has emerged as an efficient approach for air humidity control in building air conditioning process, in which the internally-cooled liquid desiccant dehumidifier is regarded as an energy-efficient device with high dehumidification effectiveness and cooling performance.